Electrodynamics and energy characteristics of aurora at high resolution by optical methods. Issue 6 (17th June 2016) - Dahlgren, H.; Lanchester, B. S.; Ivchenko, N.; Whiter, D. K.
Abstract: Technological advances leading to improved sensitivity of optical detectors have revealed that aurora contains a richness of dynamic and thin filamentary structures, but the source of the structured emissions is not fully understood. In addition, high‐resolution radar data have indicated that thin auroral arcs can be correlated with highly varying and large electric fields, but the detailed picture of the electrodynamics of auroral filaments is yet incomplete. The Auroral Structure and Kinetics (ASK) instrument is a state‐of‐the‐art ground‐based instrument designed to investigate these smallest auroral features at very high spatial and temporal resolution, by using three electron multiplying CCDs in parallel for three different narrow spectral regions. ASK is specifically designed to utilize a new optical technique to determine the ionospheric electric fields. By imaging the long‐lived O + line at 732 nm, the plasma flow in the region can be traced, and since the plasma motion is controlled by the electric field, the field strength and direction can be estimated at unprecedented resolution. The method is a powerful tool to investigate the detailed electrodynamics and current systems around the thin auroral filaments. The two other ASK cameras provide information on the precipitation by imaging prompt emissions, and the emission brightness ratio of the two emissions, together with ion chemistry modeling, is used to give information on the energy and energy flux of the precipitating electrons. In this paper, we discuss these measuring techniques and give a few examples of how they are used to reveal the nature and source of fine‐scale structuring in the aurora. Key Points: High‐resolution multispectral imaging is used to study the nature and source of dynamic aurora A new optical method is presented to investigate ionospheric electrodynamics by tracing plasma flows The ASK instrument also gives estimates of auroral energy and flux at unprecedented resolution